Universal hidden order in amorphous cellular geometries - Michael A. Klatt (Nature Portfolio, 2019)
Disordered hyperuniformity implies a hidden order on length scales that can be found in various amorphous materials. Klatt et al. analyse the evolution of random point patterns using Llyod’s algorithm and show that they converge to an effectively hyperuniform state regardless of the initial conditions.